PERMEABILITY OF THE OVARIAN FOLLICLE OF AEDES AEGYPTI MOSQUITOES - Anderson, Winston A. (The Rockefeller University Press, 1971)
The passage of tracers of various molecular weights into resting and vitellogenic ovarian follicles of Aedes aegypti mosquitoes was studied ultrastructurally. The outermost layer of the follicular sheath (the basement lamina) is a coarse mechanical filter. It is freely permeable to particles with molecular weights ranging from 12,000 to 500,000 (i.e. cytochrome c, peroxidase, hemoglobin, catalase, ferritin, immunoglobulin (IgG)-peroxidase, iron dextran and Thorotrast) that have dimensions less than 110 A. Molecules as large as carbon (300–500 A) are totally excluded. Whereas proteins and polysaccharide tracers permeate the basement lamina with apparent ease, certain inert particles (e.g. Thorotrast, Fellows-Testager Div., Fellows Mfg. Co., Inc., Detroit, Mich.) penetrate more slowly. With respect to the tracers tested, resting follicles are as permeable as vitellogenic follicles. The follicle epithelium of resting or vitellogenic follicles is penetrated by narrow intercellular channels. Our observations suggest that these spaces are lined with mucopolysaccharide material. After permeating the basement lamina, exogenous tracers fill these channels, while the bulk of material accumulates in the perioocytic space. Within 3 hr after imbibing blood, the pinocytotic mechanism of the oocyte is greatly augmented. Pinocytosis is not selective with regard to material in the perioocytic space, since double tracer studies show that exogenous compounds are not separated, but are incorporated into the same pinocytotic vesicle. During later stages of vitellogenesis, 36–48 hr after the blood-meal, the pinocytotic mechanism of the oocyte is diminished. Simultaneously, the intercellular channels become occluded by desmosomes, and the vitelline membrane plaques separate the oocyte and follicle epithelium.